PENGARUH SOCIAL MEDIA MARKETING, CONTENT MARKETING DAN BRAND IMAGE TERHADAP REPURCHASE INTENTION (STUDI PADA PELANGGAN UMKM COMEL BUCKET DENPASAR) - Sherly Echa Rachmawati; Ni Made Wulandari Kusumadewi (Jurnal Ekonomi dan Bisnis, 2026)
The development of digital marketing encourages business actors, including SMEs, to utilize various marketing strategies to retain customers and increase repeat purchases. This study aims to analyze the influence of Social Media Marketing, Content Marketing, and Brand Image on Repurchase Intention (Study on customers of Comel Bucket SMEs in Denpasar). The method used is a quantitative approach with non-probability sampling technique through purposive sampling of 112 respondents who are customers of Comel Bucket SMEs. Data were collected using questionnaires and analyzed through descriptive statistical analysis as well as multiple linier regression analysis with the help of IBM SPSS Statistics software. The research results indicate that social media marketing, content marketing, and brand image have a positive and significant influence on repurchase intention. The theoretical implication of this research is to strengthen the development of theory in the field of marketing management, especially concerning social media marketing, content marketing, and brand image, which have a positive significant impact on shaping customer perceptions of repurchase intention, as well as reinforcing the Theory of Planned Behaviour in the digital marketing context. The practical implication is to provide input for Comel Bucket SMEs in designing marketing strategies focused on enhancing social media marketing, content marketing, and brand image to drive customer repurchase intention.